The Relationship between Learning Independence and Learning Motivation with Student Academic Achievement - Isa, Abdullah (Journal of Education Method and Learning Strategy, 2023)
Learning independence and learning motivation is very important to student academic achievement. Many efforts have been made to improve student achievement in the Nursing Diploma Study Program at the University of Timor, but the results have not been as expected. This study aims to identify the relationship between learning independence and learning motivation with the academic achievement of students of Unimor Nursing Study Program. The method used is descriptive and correlative with the cross-sectional approach. The sample was Unimor Nursing Diploma Study Program students, recruited by a total sampling of 46 people. The results showed that forty-six students of the Nursing Study Program at the University of Timor completed a questionnaire containing a Liker scale of 1-5 for learning independence and learning motivation. Student academic achievements are obtained from the academic division of the Nursing Diploma Study Program. Pearson Chi-Square analysis at an alpha of 0.05 shows that there is no relationship between learning independence and learning motivation with student academic achievement [p-value> 0.05]. The conclusion is that there is no relationship between learning independence and learning motivation with the academic achievement of students of the University of Timor Nursing Study Program.